Implementasi digitalisasi manajemen pengelolaan zakat di baznas kota Pontianak: tranparansi, efektivitas layanan dan tantangan literasi digital - Siti Oktaviani (J-MD Jurnal Manajemen Dakwah, 2025)
The rapid advancement of digital technology has transformed the governance of Islamic philanthropic institutions, including zakat management. Digitalization has become a strategic necessity to enhance transparency, accountability, and service efficiency in zakat institutions, particularly at the regional level. This study aims to examine the implementation of digitalized zakat management at BAZNAS Pontianak City, focusing on its contribution to transparency and service effectiveness, as well as identifying the challenges related to community digital literacy. This research employs a descriptive qualitative approach. Data were collected through in-depth interviews with zakat management staff, direct observation of internal digital systems, and documentation analysis. Data analysis followed the Miles and Huberman model, involving data reduction, data display, and conclusion drawing, supported by source and method triangulation. The findings indicate that zakat collection and distribution processes at BAZNAS Pontianak City have been effectively digitized through an internal real-time transaction recording system. Digitalization has improved administrative efficiency, accelerated reporting, and strengthened transparency and institutional accountability. However, significant challenges remain, particularly the low level of digital literacy among muzakki and mustahik, especially elderly groups, and the absence of an official, nationally integrated digital zakat application. The study highlights the need for comprehensive digital literacy programs and the development of an inclusive, integrated zakat digital platform to ensure the sustainability of digital zakat governance. Strengthening collaboration between regional and central zakat authorities is essential to optimize digital transformation and expand public trust. This study offers empirical evidence from a regional zakat institution by integrating digital governance, service effectiveness, and digital literacy challenges into a single analytical framework, thereby contributing to the limited literature on localized digital zakat management practices in Indonesia.